PENGARUH PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN DI PT. PP. LONDON SUMATERA INDONESIA KEC. BULUKUMPA KAB. BULUKUMBA - Fadli Yudistira; Siti Hasbiah; Zainal Ruma; Abdi Akbar; Tenri S.P. Dipoatmodjo (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to determine the effect of providing incentives on employee performance at PT. PP. London Sumatra Indonesia Bulukumpa District, Bulukumba Regency. The problem in this study is that the company's production decreases every year due to declining employee performance because there are still employees who neglect the responsibilities given by the company. The benefit of this research is to be taken into consideration by the company in identifying problems so that prevention and solving of these problems can be carried out. The type of research used is quantitative using a simple regression analysis method. The population and sample in this study are all employees at PT. pp. London Sumatra Indonesia Bulukumpa District Bulukumba Regency which amounted to 40 people. The data collection technique used is a questionnaire. so that it can be concluded that if the provision of incentives is given to employees appropriately, it will make employees more enthusiastic and active at work so that employee performance will also increase.